Roots and resilience: Tracing the rise of conservative Islamic movements in Indonesia - Marom, Ahmad Anfasul; Mukmin, Budi Ali; Disyacitta, Fikri (Universitas Negeri Yogyakarta, 2026)
Although Indonesia is not formally an Islamic state, the idea of establishing one has remained a recurring theme in the country’s political discourse. From the pre-independence period to the reform era, discussions surrounding the Islamic state have persisted and never entirely disappeared. The notion continues to develop, reflecting the aspirations of certain segments of Indonesia's Muslim population. These groups, often referred to as conservative Islamic factions, are characterised by their adherence to textual interpretations of Islamic teachings and their desire to integrate religion and state within a legal and governmental framework. The emergence of conservative Islamic groups in Indonesia was not spontaneous. Rather, their development follows a long historical trajectory traceable to the pre-independence or nationalist movement period, when the country was still under colonial rule. During this era, the embryonic idea of an Islamic state began to form within Sarekat Islam (SI), then the largest Islamic organisation in the archipelago. SI would later serve as a precursor to the rise of other Islamic movements, such as Masyumi and DI/TII, which also pursued the formal integration of religion into state structures. However, the aspirations of these conservative Islamic groups for an independent Indonesia grounded in Islamic principles were ultimately thwarted during the BPUPKI session on June 1, 1945, when Pancasila was adopted as the philosophical foundation of the Indonesian state.